Characterization and adsorption efficiency of the natural and the modified diatomite via the low temperature hydrothermal route - Pookmanee P. (2014)
Natural diatomite was modified by manganese chloride via the low temperature hydrothermal route. The chemical properties and adsorption efficiency of the natural and the modified diatomite were characterized. The chemical compositions of the natural and the modified diatomite were determined by X-ray fluorescence spectroscopy (XRF) and energy dispersive X-ray spectrometry (EDXS). Morphology of the natural and the modified diatomite was investigated by scanning electron microscopy (SEM). The adsorptions of Cd(II) and Pb(II) ions onto the natural and the modified diatomite were determined by atomic absorption spectroscopy (AAS). © (2012) Trans Tech Publications.